RBM10: Harmful or helpful‐many factors to consider - Loiselle, Julie J. (J Cell Biochem, 2018)
RBM10 is an RNA binding motif (RBM) protein expressed in most, if not all, human and animal cells. Interest in RBM10 is rapidly increasing and its clinical importance is highlighted by its identification as the causative agent of TARP syndrome, a developmental condition that significantly impacts affected children. RBM10's cellular functions are beginning to be explored, with initial studies demonstrating a tumor suppressor role. Very recently, however, contradictory results have emerged, suggesting a tumor promoter role for RBM10. In this review, we describe the current state of knowledge on RBM10, and address this dichotomy in RBM10 function. Furthermore, we discuss what may be regulating RBM10 function, particularly the importance of RBM10 alternative splicing, and the relationship between RBM10 and its paralogue, RBM5. As RBM10‐related work is gaining momentum, it is critical that the various aspects of RBM10 molecular biology revealed by recent studies be considered moving forward. It is only if these recent advances in RBM10 structure and function are considered that a clearer insight into RBM10 function, and the disease states with which RBM10 mutation is associated, will be gained.